MODIFICATION OF SPARING URANOPLASTY, PREVENTING CHANGES IN THE TOPOGRAPHIC STRUCTURE OF THE EUSTACHIAN TUBE (Academicia Globe: Inderscience Research, 2022)
Congenital cleft palate is one of the most severe forms of malformations of the maxillofacial region. Preoperative orthodontic preparation is necessary for successful primary early or bicycle surgery. With early veloplasty before cheiloplasty, the strength of muscles and scars leads to the expansion of the cleft lip. Early performed cheiloplasty leads to a decrease in pathological changes in the tissues of the nasopharyngeal space.